The Comparison of Marital Property Division Between Indonesia and Malaysia from the Perspective of Fiqh Rules - Alimuddin, Harwis; Syaifuddin; Sucipto (MUI Sulawesi Selatan, 2025)
The regulations regarding the division of marital property post-divorce in Indonesia and Malaysia are the result of the juristic interpretation by scholars that has been adjusted to the socio-cultural context of the society and subsequently legislated into law. The regulations governing the division of marital property post-divorce in Indonesia refer to Law No. 1 of 1974 articles 34—37 and the Compilation of Islamic Law (KHI) articles 85-97, while in Malaysia it refers to Act 303 Islamic Family Law (Federal Territories) 1984. The majority of scholars in Indonesia and Malaysia analogize it to shirkah abdan (partnership in skill). This research is a literature study using a normative research type with a comparative study approach using the analysis of the principle of al-kharaj bi al-dhaman. This fiqh rules desire that the right to profit must be proportional to the obligation to bear risks. This principle is generally used in matters of transactions. Therefore, if the marital relationship in marital property is analogized to shirkah abdan, then it is only appropriate that this principle can also be applied in the rules of marital property division between spouses. This study concludes that the division of marital property in Indonesia, which adopts a civil law legal system, tends to divide marital property equally. Meanwhile, in Malaysia, which adopts a common law system, it considers the contributions made by the husband or wife. Through the analysis of the principle of al-kharaj bi al-dhaman , the provisions regarding the division of marital property post-divorce by considering the contributions of the husband or wife in marital property are more relevant to this principle.